Analisis dan Identifikasi Hygiene Factors dan Pengaruhnya terhadap Kepuasan Kerja pada Mitra Kerja PT. PLN UIP Nusa Tenggara - Embun Suryani; Sri Wahyulina; Siti Aisyah Hidayati (Universitas Mataram, 2020)
This study aims to identify hygiene factors and analyze their effects on job satisfaction. The data collection method in this study is a survey method, using a questionnaire as a data collection tool. The population in this study were all employees at the staff level and executors/non-staff of PT. PLN UIP Nusra consists of PT. PP Wartsila, PT. Hydro Techno Utama, and PT. Purnama Indonesia. Employees at the staff and executive/non-staff level are 75 people. At the same time, the determination of the sample is done by using accidental sampling method with a total sample of 50 people. The research variables consist of independent variables in the form of dimensions of hygiene factors and the dependent variable in the form of job satisfaction. Data analysis procedures in this study were divided into three stages, namely: 1) Conducting an importance-performance; 2) analysis (IPA) on the dimensions of hygiene factorsConducting analysis Crosstabs (cross table); 3) Conducting multiple regression analyzes. The results of data analysis showed that overall the quality performance of the dimension hygiene factors was in a proper category. Then, an analysis of the level of employee job satisfaction shows that the employees of PT. PLN UIP Nusra shows job satisfaction. Meanwhile, the results of multiple linear regression analysis showed that the variable hygiene factors and motivating factors had a positive and significant effect on the level of employee job satisfaction at PT. PLN UIP Nusra.